2008
DOI: 10.1111/j.1525-1470.2008.00685.x
|View full text |Cite
|
Sign up to set email alerts
|

An Infant with Netherton Syndrome and Persistent Pulmonary Hypertension Requiring Extracorporeal Membrane Oxygenation

Abstract: Netherton syndrome is a rare genodermatosis characterized by ichthyosiform scaling, hair shaft abnormalities, and atopic features. Affected infants typically have delayed growth and development, immune abnormalities with recurrent infections, and intermittent aminoaciduria. We report a 23-day-old girl who presented with severe primary pulmonary hypertension, exfoliative erythroderma, and trichorrhexis invaginata. Genetic studies confirmed a premature termination mutation R350X in exon 12 of SPINK5. This mutati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 20 publications
(22 reference statements)
1
2
0
1
Order By: Relevance
“…He carried this mutation as well as another nonsense mutation p.Y126*, who failed to thrive at the age of 6 months . The terminal mutation p.R350* carried by P32 was reported in a homozygous infant with persistent pulmonary hypertension . Relatively, P30 with homozygous mutation p.K754* suffered from later truncation of LEKTI, received a relatively better prognosis both in literature and in our case.…”
Section: Discussionsupporting
confidence: 48%
“…He carried this mutation as well as another nonsense mutation p.Y126*, who failed to thrive at the age of 6 months . The terminal mutation p.R350* carried by P32 was reported in a homozygous infant with persistent pulmonary hypertension . Relatively, P30 with homozygous mutation p.K754* suffered from later truncation of LEKTI, received a relatively better prognosis both in literature and in our case.…”
Section: Discussionsupporting
confidence: 48%
“…A few cases of neonatal respiratory insufficiency and pulmonary hypertension have been described in NS. Macknet et al ( 67 ) reported an infant who received extracorporeal membrane oxygenation treatment for persistent pulmonary hypertension that was probably secondary to bronchopneumonia due to the thickness of the amniotic fluid enclosing exfoliated epidermal cells. Okulu et al ( 68 ) described a newborn who required invasive respiratory support, surfactant and bronchodilators due to respiratory insufficiency and mild pulmonary hypertension.…”
Section: Resultsmentioning
confidence: 99%
“…Macknet et al, informaron sobre el caso de un lactante con SN que fue tratado con ECMO por una hipertensión pulmonar persistente que se supuso secundaria a una bronconeumonía debido al líquido amniótico espeso, que contenía células epidérmicas exfoliadas. 4 Nuestro paciente fue intubado, recibió surfactante enseguida después de nacer y fue derivado a nuestra unidad para recibir tratamiento con ECMO. Dada la hipertensión pulmonar leve, el lactante fue tratado con terapias convencionales.…”
Section: Discussionunclassified